Desarrollo de paletas cromáticas basadas en los aspectos del patrimonio intangible de la Provincia de Cotopaxi - Panchi Maigualca, Iván Santiago (2024)
This research addresses the problem faced by visual artists and graphic designers in understanding the meaning of color. Therefore, a process is carried out to create a color palette based on cultural photographs and natural landscapes, with the objective of developing the visual identity of the Province of Cotopaxi. The central problem was addressed using research tools, in addition to collecting information from primary and secondary sources to obtain specific data on the final graphic design based on the color palettes. The research is classified as descriptive and explanatory, depending on the criteria established for the study, and will be conducted using mixed methods. Once information has been gathered on the color combinations used with the selected photographs, we seek to describe all aspects important to visual perception. If we consider the theoretical and practical research, we can conclude that the methods used to obtain a chromatic palette are very restrictive. So far, it has not been possible to develop an exclusive color palette for the province of Cotopaxi that can be used in different digital or printed media, with a defined color code. For this purpose, we propose the creation of a manual or catalog that includes photographs of the festivities and natural landscapes of the province of Cotopaxi. These images will show a wide variety of characteristic colors, which highlights the importance of the project by generating an identity through innovation in the selection of colors, facilitating the creation of unique and personalized designs.